Organizational forms of coordination and integration of activities in project management - Skalik, Jan (Zielona Góra: Faculty of Economics and Management Press)
Solving the problems connected to coordination in managing complex projects is crucial for their successful completion. The paper discusses organizational forms of coordination in implementing a project and the factors that should be considered when selecting them, so that the amount of coordinating potential generated by the chosen form is proportionate to the actual needs in this field.
Keywords: zarządzanie projektami; koordynacja; organizacja koordynacji; project management; coordination